Institutional Ethnography: An Approach to Explicate the Ruling Relations in Healthcare Institutions - Farzaneh Mokhtary; Abouali Vedadhir; Akram Sanagoo; Leila Jouybari (نشریه پرستاری ایران)
Background & Aims Institutional ethnography (IE), as one of the qualitative approaches, focuses on the everyday work processes of individuals. In this study, we aim to introduce the IE for explicating the relations in the healthcare institutions. This study will investigate the key terms, concepts, and insights of IE through examples by reviewing the related studies. Materials & Methods This methodological study involved a search in databases including PubMed, Scopus, Web of Science, Cochrane Library, the Iranian Scientific Information Database (SID), and Google Scholar using the keywords institutional ethnography, IE, healthcare system, and delivery of health care, without any time limit until January 2024. Results The IE has four steps: identifying the disjuncture and problematic, data collection, data analysis, and recommendations and conclusions useful for changing practice. In this approach, the institutional ethnographer utilizes a wide range of data collection techniques, including interviews, observations, focus group discussions, document collection, and reflexivity to create a description of what people do in their everyday lives. Conclusion The IE is used to identify and understand how higher-level processes and policies impact daily clinical work. Achieving a proper understanding of how texts and individuals function together within an organization (what actually happens) enables the formulation and implementation of practical strategies for addressing issues in the field.